Long‐acting somatostatin analogues provide significant beneficial effect in patients with refractory small bowel angiodysplasia: Results from a proof of concept open label mono‐centre trial. Issue 1 (1st February 2016) - Holleran, Grainne; Hall, Barry; Breslin, Niall; McNamara, Deirdre
Abstract : Introduction: Small bowel angiodysplasias account for over 50% of causes of small bowel bleeding and carry a worse prognosis than lesions located elsewhere in the gastrointestinal tract. Re‐bleeding rates are high even after first‐line endoscopic therapy and are associated with high levels of morbidity for affected patients. Small trials of long‐acting somatostatin analogues have shown promising results but have not yet been assessed in patients with refractory small bowel disease. Aim: The purpose of this study was to assess the effect of long‐acting somatostatin analogues in reducing re‐bleeding rates and transfusion requirements, and improving haemoglobin levels in patients with refractory small bowel angiodysplasia. Methods: Patients with refractory small bowel angiodysplasia were treated with 20 mg of long‐acting octreotide for a minimum of three months. Response was assessed according to: rates of re‐bleeding, haemoglobin levels, transfusion requirements, and side effects. Results: A total of 24 patients were initially treated and 20 received at least three doses. Rates of complete, partial and non‐response were 70%, 20% and 10% respectively. Average haemoglobin rates increased from 9.19 g/dl to 11.35 g/dl ( p  = 0.0027, 95% confidence interval (CI) −3.5 to −1.1) in the group overall and 70% remained transfusion‐free after a mean treatment duration of 8.8 months. The rate of adverse events was higher than previously reported at 30%. Conclusion: Long‐acting somatostatin analogues offer a therapeutic advantage in a significant proportion of patients with small bowel angiodysplasia. With careful patient selection and close observation, a long‐acting somatostatin analogue should be considered in all patients with persistent anaemia attributable to refractory disease in conjunction with other standard treatments.